Tenuazonic Acid-Triggered Cell Death Is the Essential Prerequisite for Alternaria alternata (Fr.) Keissler to Infect Successfully Host Ageratina adenophora - Shi, Jiale (Cells, 2021)
The necrotrophic fungus Alternaria alternata contains different pathotypes that produce different mycotoxins. The pathotype Ageratina adenophora secretes the non-host-selective toxin tenuazonic acid (TeA), which can cause necrosis in many plants. Although TeA is thought to be a central virulence factor of the A. adenophora pathotype, the precise role of TeA in different stages of host infection by pathogens remains unclear. Here, an A. alternata wild-type and the toxin-deficient mutant ΔHP001 with a 75% reduction in TeA production were used. It was observed that wild-type pathogens could induce the reactive oxygen species (ROS) bursts in host leaves and killed photosynthetic cells before invading hyphae. The ROS interceptor catalase remarkably inhibited hyphal penetration and invasive hyphal growth and expansion in infected leaves and suppressed necrotic leaf lesion. This suggests that the production of ROS is critical for pathogen invasion and proliferation and disease symptom formation during infection. It was found that the mutant pathogens did not cause the formation of ROS and cell death in host leaves, showing an almost complete loss of disease susceptibility. In addition, the lack of TeA resulted in a significant reduction in the ability of the pathogen to penetrate invasive hyphal growth and spread. The addition of exogenous TeA, AAL-toxin, and bentazone to the mutant ΔHP001 pathogens during inoculation resulted in a significant restoration of pathogenicity by increasing the level of cell death, frequency of hyphal penetration, and extent of invasive hyphal spread. Our results suggest that cell death triggered by TeA is the essential requirement for successful colonization and disease development in host leaves during infection with A. adenophora pathogens.